2020
DOI: 10.1108/mrjiam-06-2019-0931
|View full text |Cite
|
Sign up to set email alerts
|

Individual bicultural identity and cultural intelligence

Abstract: Purpose This paper aims to examine the relationship between individual bicultural identity and attitudes toward diversity. The authors also theorize and test the mechanism through which individual bicultural identity will be more likely to result in positive attitudes toward diversity. Design/methodology/approach The authors collected survey data drawing from two different samples and two different measures of attitudes toward diversity. To test the hypotheses, the authors conducted structural equation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Korzilius et al, 2017), attitudes toward diversity (e.g. Wagstaff et al, 2020) and intercultural effectiveness (e.g. Thomas et al, 2010).…”
Section: Contribution and Practical Implications Contributionmentioning
confidence: 99%
“…Korzilius et al, 2017), attitudes toward diversity (e.g. Wagstaff et al, 2020) and intercultural effectiveness (e.g. Thomas et al, 2010).…”
Section: Contribution and Practical Implications Contributionmentioning
confidence: 99%
“…First, because CQ is a newly emerging intelligence, it is underresearched. It has been also studied mainly in specific contexts such as international business and education (e.g., Ang & Van Dyne, 2008; Wagstaff et al, 2020). We expanded the boundary of prior study contexts by presenting CQ as an effective personal resource for domestic (hospitality) employees who serve diverse customers.…”
Section: Discussionmentioning
confidence: 99%
“…Like other types of intelligence (e.g. cognitive, emotional, or social) that are typically related to the capability to complete tasks, CQ may indicate the attitudinal or behavioral outcomes of an individual (e.g., Ang et al, 2007; Wagstaff et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with international research (Nguyen & Benet‐Martínez, 2013) our study suggest that some form of biculturalism would be optimal for foreign workers in Denmark. Wagstaff, Kim, Arévalo, Al‐Riyami and Huerta (2020) found that cultural intelligence partially mediated the association between bicultural identity and positive attitudes toward cultural diversity, suggesting CQ as a central mechanism in managing one’s cultural affiliation and openness to destination cultural streams within multicultural work environments.…”
Section: Discussionmentioning
confidence: 99%